Reconstructing a Prehistoric Fish Trap - Eva IJsveld (EXARC, 2014)
Fish traps, still in use all over the world today for catching fish and crustaceans, have been used by mankind at least since the Mesolithic period. Their shape at that time is quite well-established, suggesting that they may have originated even earlier (Bulten et al, 2002: 108). This type of fish trap is made up of two elements: the funnel and the main trap body (or pot). The funnel is placed in the opening of the trap, pointing inwards to guide the fish into the trap and prevent their exit.